2020
DOI: 10.1029/2019jb018864
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mineral Precipitation During Shear Fracturing of Carbonate‐Rich Shales

Abstract: Target subsurface reservoirs for emerging low-carbon energy technologies and geologic carbon sequestration typically have low permeability and thus rely heavily on fluid transport through natural and induced fracture networks. Sustainable development of these systems requires deeper understanding of how geochemically mediated deformation impacts fracture microstructure and permeability evolution, particularly with respect to geochemical reactions between pore fluids and the host rock. In this work, a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
(80 reference statements)
2
19
0
Order By: Relevance
“…The precipitation studies of Menefee et al. (2020) illustrate communication between the primary fracture and the damaged matrix (Figure 4). The sorption behavior of tracers has also been used to interrogate fracture surface area (Dean et al., 2015; Roshan et al., 2016).…”
Section: Laboratory Experimentsmentioning
confidence: 95%
See 4 more Smart Citations
“…The precipitation studies of Menefee et al. (2020) illustrate communication between the primary fracture and the damaged matrix (Figure 4). The sorption behavior of tracers has also been used to interrogate fracture surface area (Dean et al., 2015; Roshan et al., 2016).…”
Section: Laboratory Experimentsmentioning
confidence: 95%
“…They observed substantial reductions of permeability due to dissolution of asperities confirmed by X-ray CT. On the other hand, experiments with HCl on highly reactive limestone showed in one case strong increases in permeability (Noiriel et al, 2013) and, in another case, complex wormhole evolution with strongly enhanced permeability with increasing flow rates (Noiriel & Deng, 2018). In experiments that involve the potential for both dissolution and precipitation, Dávila et al (2016) found that competing calcite dissolution and gypsum precipitation resulted in little change to permeability, while Menefee et al (2020) found extensive precipitation during competing calcite dissolution and witherite (BaCO 3 ) precipitation that concentrated in tight regions of the fracture and within comminuted fracture material (Figure 4). Menefee et al (2020) observed relatively small to negligible decreases in permeability.…”
Section: Chemical Reactions and Fracture Flow (T-h-c)mentioning
confidence: 99%
See 3 more Smart Citations